Daily allergic multimorbidity in rhinitis using mobile technology: A novel concept of the MASK study - Bousquet, J.; Devillier, P.; Anto, J. M.; Bewick, M.; Haahtela, T.; Arnavielhe, S.; Bedbrook, A.; Murray, R.; van Eerd, M.; Fonseca, J. A.; Morais Almeida, M.; Todo Bom, A.; et al. (Allergy (Copenhagen), 2018)
Background Multimorbidity in allergic airway diseases is well known, but no data exist about the daily dynamics of symptoms and their impact on work. To better understand this, we aimed to assess the presence and control of daily allergic multimorbidity (asthma, conjunctivitis, rhinitis) and its impact on work productivity using a mobile technology, the Allergy Diary. Methods We undertook a 1‐year prospective observational study in which 4 210 users and 32 585 days were monitored in 19 countries. Five visual analogue scales (VAS) assessed the daily burden of the disease (i.e., global evaluation, nose, eyes, asthma and work). Visual analogue scale levels <20/100 were categorized as “Low” burden and VAS levels ≥50/100 as “High” burden. Results Visual analogue scales global measured levels assessing the global control of the allergic disease were significantly associated with allergic multimorbidity. Eight hypothesis‐driven patterns were defined based on “Low” and “High” VAS levels. There were <0.2% days of Rhinitis Low and Asthma High or Conjunctivitis High patterns. There were 5.9% days with a Rhinitis High—Asthma Low pattern. There were 1.7% days with a Rhinitis High—Asthma High—Conjunctivitis Low pattern. A novel Rhinitis High—Asthma High—Conjunctivitis High pattern was identified in 2.9% days and had the greatest impact on uncontrolled VAS global measured and impaired work productivity. Work productivity was significantly correlated with VAS global measured levels. Conclusions In a novel approach examining daily symptoms with mobile technology, we found considerable intra‐individual variability of allergic multimorbidity including a previously unrecognized extreme pattern of uncontrolled multimorbidity.